New perspectives on HTML, XHTML, and dynamic HTML : - Carey, Patrick (Thomson, 2006)
Part of the New Perspectives Series, this text teaches students HTML and XHTML using a simple text editor to create basic to complex Web sites. Advanced tutorials on DHTML help students to further their skills by learning and applying DHTML to make interactive features such as animated text, image rollovers, menus, and expandable outlines.